Students' satisfaction level towards service delivery of Academic Affairs Department, UiTM Sarawak / Nurul Huda - Huda, Nurul; Jam, Sang (2014)
Today, service quality is very important to the service provider and the service consumer. They are for the enjoyment of competitive advantages of organizations which shows increasing attention to the quality issue. Service quality is a stable criterion that indicates how the presented services correspond with the clients’ expectations. Customer satisfaction will be affected by a strong form of the nature customer contact and interaction between companies and customers. The study examines the level of students’ satisfaction on service quality provided by Academic Affairs Department of UiTM Sarawak, Samarahan 1 campus. It was also to examine the relationship between students' satisfaction and service quality. Apart from that, it was also to identify the most important service quality variable for students’ satisfaction. Questionnaires were developed for the purpose of the data collection. Out of 278 student’s population, 162 students were involved in this study. The data was analyzed using IBM Statistical Package for Social Science (SSPS) version 20 software. The service quality and students’ satisfaction level was examined and found out to be moderate. Bivariate Pearson Correlation was performed on the data in order to determine whether there is a significant relationship between service quality and students’ satisfaction. The findings shows that they are strong correlated. Among the five variables, empathy is the most important one in determining satisfaction among students despite of all the other variables that was assurance, responsiveness, tangible, and reliability. The researcher recommends that the study could be extended to the Samarahan 2 campus so that the data could represent the whole Academic Affairs Department of UiTM Sarawak, Samarahan Campus. From this study, the findings may be useful for the management of UiTM and other institutions in the market by emphasizing the major elements that affect the satisfaction level among students. Furthermore, the outcomes of this study will assist the management of these institutions in figure out the flaws to be improve on and they could highlighted points that should be maintain in order to become the top service quality provider in the higher learning institution.